Examination Of The Changes In The Spatial Usage Of The Passages And The Behaviors Of Their Consumers Between 2008 And 2019: The Case Of Ankara Kızılay - Özcan, Kübra Yıldırım (Fırat University, 2022)
The changing spatial uses and consumer behaviors with the developing technology between 2008-2019 have affected the global and local markets. The passages in the city, which were heavily used by consumers in the previous years, have been replaced by the use of big shopping centers and even e-commerce areas in recent years. The main purpose of the study is to examine how consumer behaviors are reflected in the use of space in two passages in Ankara Kızılay. The aim of the study is to examine how consumer behaviors are reflected in the space in the passages chosen as the samples and in this context, to reveal whether the original spatial characters have changed between 2008 and 2019. In this direction, the scope of the study is whether the new economic and physical conditions that emerged between 2008-2019, the changing consumer behavior with the developing technology have an impact on the reconfiguration of the spaces in the aforementioned passages and to determine whether the original spatial characters of these passages have changed with the aforementioned factors. In this context, the face-to-face surveys, interviews and observation studies conducted in the study areas in 2008 were repeated and compared in 2019 in the same way. As a result of the study, it has been determined that the changing consumer behaviors with the developing technology has an effect on the economic situation in the passages and the intensity of use of the passages by the individuals. In particular, it has been observed that one of the passages has relatively lost its feature of being a passage and predominantly they have become shopping places used by certain consumer groups and also the aforementioned passages have become places where more certain products are sold.

2008-2019 yılları arasında gelişen teknoloji ile değişen mekânsal kullanımlar ve tüketici davranışları küresel ve yerel piyasaları etkilemiştir. Daha önceki yıllarda tüketiciler tarafından yoğun olarak kullanılan kent içerisindeki pasajların yerini son yıllarda büyük alışveriş merkezleri ve hatta e-ticaret alanlarının kullanımı almıştır. Çalışmanın temel amacı Ankara Kızılay'da yer alan iki adet pasajda, tüketici davranışlarının mekan kullanımına nasıl yansıdığının irdelenmesidir. Çalışmanın hedefi ise örneklem olarak seçilen pasajlarda tüketici davranışlarının mekana nasıl yansıdığının irdelenmesi ve bu çerçevede özgün mekânsal karakterlerinin 2008 ve 2019 yılları arasında değişip değişmediğinin ortaya konulmasıdır. Bu doğrultuda çalışmanın kapsamı ise, söz konusu pasajlarda, 2008-2019 yılları arasında oluşan yeni ekonomik ve fiziksel koşulların, gelişen teknoloji ile değişen tüketici davranışlarının mekanların yeniden kurgulanmasında etki edip etmediğinin ve bu pasajların özgün mekânsal karakterlerinin bahsi geçen etkenlerle değişip değişmediğinin belirlenmesidir. Bu kapsamda, 2008 yılında çalışma alanlarında yüz yüze yapılan anketler, görüşmeler ve gözlem çalışmaları, 2019 yılında aynı şekilde tekrarlanarak karşılaştırılmıştır. Çalışma sonucunda gelişen teknoloji ile değişen tüketici davranışlarının pasajlardaki ekonomik durum ve bireylerin pasajları kullanım yoğunluğu üzerinde etkili olduğu tespit edilmiştir. Özellikle pasajlardan birinin geçit olma özelliğini nispeten kaybettiği ve ağırlıklı olarak belirli tüketici gruplarının kullandığı alışveriş mekanları haline geldiği ve ayrıca bahsi geçen pasajlarda daha çok belirli ürünlerin satıldığı gözlemlenmiştir.
2008 VE 2019 YILLARI ARASINDA PASAJLARIN MEKANSAL KULLANIMINDAKİ VE TÜKETİCİLERİNİN DAVRANIŞLARINDAKİ DEĞİŞİKLİKLERİN İNCELENMESİ: ANKARA KIZILAY ÖRNEĞİ